ARTIKEL REVIEW: PEMANFAATAN KATALIS ZEOLIT ALAM TERAKTIVASI DALAM SINTESIS BIODIESEL DENGAN METODE ESTERIFIKASI DAN TRANSESTERIFIKASI - Siti Novita Sari Ulfa; Samik Samik (Unesa Journal of Chemistry, 2022)
The depletion of petroleum fuels can become a problem if not addressed quickly. This can lead to scarcity and an increase in the price of fuel oil. Alternative energy has begun to be developed as a solution to this problem, one of which is biodiesel. Biodiesel synthesis has the main ingredient in the form of oils such as palm oil, used cooking oil, rubber seed oil, crude palm oil, and others. The biodiesel synthesis reaction is a transesterification reaction that tends to be slow and long, so a catalyst is needed so that the reaction can run quickly. There are two catalysts that can be used, namely homogeneous catalysts and heterogeneous catalysts. The use of heterogeneous catalysts is easier because at the end of the reaction they can be separated easily. One of the heterogeneous biodiesel catalysts that can be used is natural zeolite catalyst. The use of natural zeolite catalysts has many advantages such as its relatively cheap price, abundant abundance in nature, and environmental friendliness. Utilization of natural zeolite as a biodiesel catalyst requires the activation of natural zeolite which can be carried out with acid or alkaline solutions. Therefore, in this review article, we discuss the % yield of biodiesel with the help of natural zeolite catalysts which are activated by acid or base from ten articles. The highest % biodiesel yield was obtained at 100% in the production of biodiesel from used cooking oil with an acid-activated Wonosari natural zeolite catalyst in the form of 6M HCl in an esterification reaction of 2% by weight of oil. Then proceed with the transesterification reaction with KOH as a base catalyst at a temperature of 60℃ with a molar ratio of oil and methanol 1:6 for 1 hour, and stirring speed of 1200 rpm. Based on the results of this review article, natural zeolite that has been activated by acid or base can be used as a catalyst in biodiesel synthesis using the transesterification and esterification method. Key words: Biodiesel, Biodiesel Catalyst, Natural Zeolite